Supramolecular chemistry in solid state materials such as metal-organic frameworks - Fracaroli, Alejandro Matías (2018)
Supramolecular chemistry has enriched the scientific research for more than fifty years reaching one of its summits in 2016, when the Chemistry Nobel Prize was awarded for the design and synthesis of molecular machines, in which host-guest chemistry plays a fundamental role. Recently, the groups of Omar Yaghi and Fraser Stoddart, among others, have demonstrated that this chemistry can be extended to the pores of metal-organic frameworks (MOFs). This heterogenization of supramolecular chemistry can be achieved through the incorporation of macrocycles to the organic struts of these highly porous and crystalline materials. Throughout this short review we summarize interesting examples of selective recognition by naturally occurring and synthetic macrocycles in solution and solid state; and later we survey important milestones to achieve specific recognition sites and develop host-guest chemistry at the pores of MOFs.This summary contains examples of different synthetic strategies to incorporate macrocycles to solid state materials, and in particular, to prepare supramolecular MOFs with particular properties and related applications. Specifically, the revised research includes the incorporation of both naturally occurring and synthetic macrocycles to solid state materials such as polymers, metal nanoparticles, etc., as prelude of the solid phase recognition studied in MOFs. An important number of the contributions presented here feature porous solids with smooth access to the host´s cavity incorporated in the pores, allowing specific recognition of guest molecules. This smooth access to those active recognition sites in materials with extremely high surface area such as MOFs, open the possibility to develop the next generation of frontier materials with application in fields such as selective capture of water toxins and heterogeneous catalysis, among others.